1991
DOI: 10.1016/s0022-5347(17)38427-6
|View full text |Cite
|
Sign up to set email alerts
|

A Report on Extracorporeal Shock Wave Lithotripsy Results on 1,569 Renal Units in an Outpatient Clinic

Abstract: We report our experience with extracorporeal shock wave lithotripsy (ESWL*) treatment of 1,569 renal units in an outpatient clinic with a small focused piezoelectric lithotriptor. A stone-free rate of 93% was achieved. In 3.6% of the patients, mainly those with a history of surgery and/or anatomical caliceal deformations, fragments smaller than 3 mm. in diameter remained despite multiple ESWL sessions and intensive upside down physiotherapy. Of the cases 3.4%, including those without sufficient data, were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
6

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 3 publications
2
25
1
6
Order By: Relevance
“…15 Predictive factors associated with surgical outcomes of these modalities have been reported to be total stone burden and location of stone burden. [2][3][4][5][6] Stone-free rates for SWL ranged from 45% to 99%, depending on stone location, burden, and composition. [2][3][4] Stone-free rate for PNL in a single session consisting of 180 patients was 51%, and upper pole stones and greater size have been associated with lower rates of attaining stone-free states.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Predictive factors associated with surgical outcomes of these modalities have been reported to be total stone burden and location of stone burden. [2][3][4][5][6] Stone-free rates for SWL ranged from 45% to 99%, depending on stone location, burden, and composition. [2][3][4] Stone-free rate for PNL in a single session consisting of 180 patients was 51%, and upper pole stones and greater size have been associated with lower rates of attaining stone-free states.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Stone-free rates for SWL ranged from 45% to 99%, depending on stone location, burden, and composition. [2][3][4] Stone-free rate for PNL in a single session consisting of 180 patients was 51%, and upper pole stones and greater size have been associated with lower rates of attaining stone-free states. 5 Turna et al demonstrated an overall stone-free rate of 78.6%, which decreased with increasing stone size and caliceal component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the 70s, retained stones were removed surgically by means of large incisions in the skin. After that decade, the treatment of calculi came to be undertaken by extracorporeal shockwave lithotripsy (ESWL) (1), percutaneous nephrolithotripsy (PCNL) (2-4) and endoscopic ureterolithotripsy. Today PCNL is the gold standard treatment for renal stones bigger than 2cm (5).…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been established as a safe and effective therapy for upper urinary tract calculi and has become the primary method of intervention for many urologists. [2][3][4][5][6] While serious side effects are rare, transient cardiac dysrhythmias (CD) may be associated with ESWL. [7][8][9][10][11][12] Such events have been documented at rates of 60% to 80% with early lithotripters and have led to the development of electrocardiogram (ECG)-gated shock wave delivery systems for management and prevention.…”
Section: Introductionmentioning
confidence: 99%